Rapid monitoring of heavy metals in fluvial sediments using laser-induced breakdown spectroscopy - Martino, Lucila Juliana (2019)
In this work, a quantitative analysis of heavy metals Cr and Cu in fluvial sediments was carried out by Laser-induced breakdown Spectroscopy (LIBS) to assess the anthropogenic. To perform the analysis, different sediment samples were collected at selected positions. Standard addition calibration curves were constructed for Cr and Cu by measuring the Cr I line at 357.87 nm and Cu I line at 324.75 nm. The moisture and organic matter contents of the sediments were taken into account to overcome the matrix effect. The quantitative models were evaluated statistically to evaluate the robustness and prediction ability of the method. Low values for root-mean-square errors for calibration (RMSEC), prediction (RMSEP) and cross-validation (RMSECV) were calculated. High values of the correlation coefficients of calibration (Rc2 = 0:984 for Cr; Rc2= 0:986 for Cu) and cross-validation (Rcv2 = 0:985 for Cr; Rcv2 = 0:981 for Cu) were obtained. The calculated limits of detection (LoD) were 2.9 ppm for Cr and 3.3 ppm for Cu, and the limits of quantification (LoQ) were 9.5 ppm for Cr and 11 ppm for Cu. Concentrations of Cr and Cu higher than the baseline values were obtained in the sediments downstream (Cr: 49 ppm, Cu: 81 ppm) which are indicative of the pollution of the basin by heavy metals due to the spill of untreated effluents derived from anthropogenic activities. LIBS analysis was optimized for reliable heavy metal monitoring in fluvial sediments.